GSC-DADOS: O USO DE TECNOLOGIA DA INFORMAÇÃO PARA A DISSEMINAÇÃO DE DADOS PARA O EMPODERAMENTO DA SOCIEDADE - Felipim, Danieli G.; Allebrandt, Sérgio L.; Prauchner, Darlinton C. K.; Cavalheiro, Marcos R. M.; Ri, Marlene D.; Rasia, Pedro C. (Salão do Conhecimento, 2013)
Resumo